Performance analysis and evaluation of secure password persuasive cued click points. Issue 4 (7th November 2016) - Nayak, Atish Dipakbhai; Bansode, Rajesh
Abstract : Purpose: The purpose of this paper is to increase security using persuasive cued click points (PCCP) techniques and to make a system to provide security from the malware, key loggers and attacks. Design/methodology/approach: The work methodology comprises two major phases. In phase one, the PCCP take place with the registration and login process done. It also includes text-based password which hides the character of password to protect from shoulder surfing attack. In phase two, the work includes background services which protect from key loggers. Findings: Secure password persuasive cued click point (SPPCCP) is a module that facilitates authentication for the desktop-based applications and provides a single-machine licensing functionality. SPPCCP comprises little functionality to thwart attackers, such as persuasive click points with password protection. The techniques to protect against malware such as resist from debuggers and also to the key loggers that run on desktop computers. In this, Spearman rank correlation is used for detection of key loggers. There are functionalities used to secure desktop applications such as time constraint and user selection. Originality/value: The contribution of this paper is to provide knowledge in the field of security. It makes the graphical password more secure and useful. The intention behind this research was to increase the security level up to 60-80 per cent. It is also used for prevention of shoulder surfing problem till 80 per cent; this research is also operated on key loggers, and SPPCCP finds the key loggers and removes it from the system. It also decrypts the data of database by encrypting it by SHA-512 algorithm and reduces the average login time up to 20-30 per cent; it will make a smaller view port of 33.5 × 33.5 pixel square to have more choice to select the password, thereby decreasing the probability of hotspot area up to 18-20 per cent.